Industrial And Geological Study Of Protozoic Metacarbonate Rocks From Southern And Central Nigeria - Onimisi, Jimoh Abdullateef (2017)
The metacarbonate deposits in the southern Nigeria intercalated with calc-silicate gneiss, intrusive granite and migmatite gneiss rocks are of Proterozoic age. The study focused on examining the suitability of the Okpella and Emiworo metacarbonate via characterization and synthesis for industrial applications. This study is based on X-ray Diffractometry (XRD), Scanning electron microscopy (SEM), polarizing and refracted light microscopy; chemical and differential thermal analysis/thermal gravimetric analysis (DTA/TGA) and also the physical properties of the raw marble resources and derived product. Calcite is the dominant phase while silica is the subordinating component of Okpella marble. The Okpella metacarbonate characterized by minimal water absorption, appreciable compressive strength, high loss of ignition (LOI) and bulk specific gravity (SG). The quicklime calcined at 900°C and 1100°C for 60, 90 and 120 minutes of soaking time were unreactive. However, the quicklime calcined at 1000°C exhibited high reactivity. On the other hand, the phase characteristics of the Emiworo marble show that dolomite is the dominant mineral with low silicates. Reactivity of the quicklime measured after calcination at different temperatures revealed that only the quicklime produced in 1 hour at 950°C and 1000°C was found to be more reactive. Physical properties and comparative data show that the Emiworo marble displays lower water absorption, lower compressive strength, and higher loss on ignition compared to the Okpella marble. The marble has affluent industrial applications characteristics attributed to its established microstructure, chemical composition and thermal decomposition behavior. Aloe-Vera extract was found to have an effect on the precipitated calcium carbonate (PCC) morphology, particle sizes, and thermal characteristics of the synthesized PCC. Utilizing a continuous unique tubular reactor under ambient temperature and 1 L/min CO2 flowrate, rhombohedral calcite polymorph and aragonite polymorph composite with polycrystalline dumb bell-like structure, having radiating ends was produced from Okpella marble. However, uniform hierarchical aragonite precipitated calcium carbonate stacked from nanoparticles was synthesized using a natural occurring Emiworo dolomite. The tainted Mg influence on resultant PCC purity was averted via D-glucose extraction of dolomite constituent.